2017
DOI: 10.1186/s41200-016-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of flat oyster species reveals the presence of Ostrea stentina Payraudeau, 1826 (Bivalvia: Ostreidae) in Japan

Abstract: Background: DNA barcoding is an effective method of accurately identifying morphologically similar oyster species. However, for some of Japan's Ostrea species there are no molecular data in the international DNA databases. Methods: We sequenced the mitochondrial large subunit ribosomal DNA (LSrDNA) and cytochrome c oxidase subunit I (COI) gene of five known and two unidentified Ostrea species. Phylogenetic comparison with known Ostrea species permitted accurate species identification by DNA barcoding. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…This is the first documented record of O. equestris in Hawaiian waters. The O. stentina/aupouria/equestris species complex is globally distributed, found along Atlantic coasts, the Mediterranean, North Africa, New Zealand, Japan, China, and South America (Crocetta et al 2013; Hamaguchi et al 2017; Hu et al 2019; Lapègue et al 2006; Pejovic et al 2016). At this time, it is uncertain whether O. equestris in Hawai’i is native or introduced, though it seems likely to be native given the wide distribution of O. equestris in both the Atlantic and Pacific oceans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first documented record of O. equestris in Hawaiian waters. The O. stentina/aupouria/equestris species complex is globally distributed, found along Atlantic coasts, the Mediterranean, North Africa, New Zealand, Japan, China, and South America (Crocetta et al 2013; Hamaguchi et al 2017; Hu et al 2019; Lapègue et al 2006; Pejovic et al 2016). At this time, it is uncertain whether O. equestris in Hawai’i is native or introduced, though it seems likely to be native given the wide distribution of O. equestris in both the Atlantic and Pacific oceans.…”
Section: Discussionmentioning
confidence: 99%
“…The selected models were HKY+I+G and HKY+G respectively for 16S and COI . We constructed Bayesian trees via MrBayes implemented in Geneious, using the following species for comparison: C. gigas (DQ839414, FJ743509, AY632550, JF808180, JF700177 (Pie et al 2006; Sayers et al 2018; Wang et al 2004; Zhang et al 2013)), C. gigas angulata (KC170323, KC170322 (Peng-yun 2013; Sayers et al 2018)), D. sandvichensis (KC847121, EU815985 (Sayers et al 2018)), O. angasi (AF052063 (Jozefowicz & Foighil 1998; Sayers et al 2018)), O. angelica (KT317127, KT317140, KT317449 (Raith et al 2015; Sayers et al 2018)) , O. chilensis (AF052065 (Jozefowicz & Foighil 1998; Sayers et al 2018)), O. circumpicta (MG560202 (Sayers et al 2018), O. conchaphila (KT317173, FJ768528, KT317494 (Polson et al 2009; Raith et al 2015; Sayers et al 2018)), O. denselamellosa (FJ743511, HQ660995, KP067907 (Kim et al 2015; Liu et al 2011; Sayers et al 2018)), O. edulis (JQ611449, AF540595, KJ818235 (Malkowsky & Klussmann-Kolb 2012; Morton et al 2003; Pejovic et al 2016; Sayers et al 2018)), O. futamiensis (LC051603 (Hamaguchi et al 2017; Sayers et al 2018)), O. lurida (FJ768559, FJ768554, KT317504 (Polson et al 2009; Raith et al 2015; Sayers et al 2018)), O. permollis (AY376605, AY376606, DQ226526 (Kirkendale et al 2004; Sayers et al 2018)) , O. puelchana (AF052073, DQ226521 (Jozefowicz & Foighil 1998; Sayers et al 2018)), and O. stentina/aupouria/equestris species complex (Table 3). For outgroups, we used sequences from Hyotissa imbricata (KC847136 and AB076917 (Matsumoto 2003; Sayers et al 2018)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hubert et al (2012) also revealed cryptic fish diversity in coral reefs of Indo-Malay Philippines Archipelago. Hamaguchi et al (2017) reported about cryptic diversity in flat oysters distributed in Japan.…”
Section: Dna Barcoding and Cryptic Speciesmentioning
confidence: 99%
“…This oyster has been identified as Crassostrea gigas based on shell morphology [1][2][3]. However, shell appearance is not a reliable feature for oyster identification because of high phenotypic plasticity in these bivalves [4,5]. Taking into account that the validity of C. gigas has never been genetically confirmed in Primorye, the genetic analysis of specimens seems necessary.…”
Section: Introductionmentioning
confidence: 99%